An annotated checklist of the Iranian Figitidae (Hymenoptera: Cynipoidea). (2nd July 2020) - Ghahari, Hassan; Ferrer-Suay, Mar; Mata-Casanova, Noel; Pujade-Villar, Juli
ABSTRACT: An annotated list of Figitidae (Hymenoptera: Cynipoidea) present in Iran is given. A total of 33 species belonging to 11 genera and five subfamilies are reported: Anacharitinae (3 genera, 4 species), Aspicerinae (2 genera, 4 species), Charipinae (3 genera, 21 species), Eucoilinae (1 species) and 'unplaced tribe' (2 genera, 3 species). Two species are excluded from the fauna of Iran as nomina dubia, and 2 species ( Phaenoglyphis longicornis (Hartig, 1840) and Melanips syrphidiphagus (Narayanan, 1941)) are new for Iran. These data show the little knowledge we have of these Hymenoptera (Figitidae) from this country; excepting the Charipinae subfamily other groups are virtually unknown.